Bridge design and evaluation : LRFD and LRFR - Fu, Gongkang (John Wiley & Sons, 2013)
BA succinct, real, world approach to complete bridge system design and evaluation/b/ Load and Resistance Factor Design (LRFD) and Load and Resistance Factor Rating (LRFR) are design and evaluation methods that have replaced or offered alternatives to other traditional methods as the new standards for designing and load, rating U.S. highway bridges. iBridge Design and Evaluation/i covers complete bridge systems (substructure and superstructure) in one succinct, manageable package. It presents real, world bridge examples demonstrating both their design and evaluation using LRFD and LRFR. Designed for a 3, to 4,credit undergraduate or graduate, level course, it presents the fundamentals of the topic without expanding needlessly into advanced or specialized topics. Important features include:ulliExclusive focus on LRFD and LRFR/liliHundreds of photographs and figures of real bridges to connect the theoretical with the practical/liliDesign and evaluation examples from real bridges including actual bridge plans and drawings and design methodologies/liliNumerous exercise problems/liliSpecific design for a 3, to 4,credit course at the undergraduate or graduate level/liliThe only bridge engineering textbook to cover the important topics of bridge evaluation and rating/li/ul iBridge Design and Evaluation/i is the most up, to, date and inclusive introduction available for students in civil engineering specializing in structural and transportation engineering.